Spirit in the dark: a religious history of racial aesthetics - Sorett, Josef (Oxford University Press, 2016)
Church, spirit, and the history of racial aesthetics -- The church and the Negro spirit -- Ancestral spirits -- Catholic spirits -- As the spirit moves -- An international spirit -- That spirit is Black -- Contrary spirits -- You can't keep a good church down!